A comparative study to estimate three commercial products of human chorionic gonadotropin (hCG) on blood biochemistry, sexual hormones concentrations, reproductive indices, and larvae production of African catfish Clarias gariepinus brood-stock - El-Sayed I. Attia; Mohamed F. A. Abdel-Aziz; Habib Ul Hassan; Mohammad Z. Ahmed; Takaomi Arai; Hamed H. E. Saleh (Italian Journal of Animal Science)
Currently, almost all hatcheries that produce catfish seeds depend on hormone stimulations, application of human chorionic gonadotropin hormone (hCG) is considered the common method for commercial spawning of African catfish Clarias gariepinus, regardless of whether they use an artificial or semi-industrial hatching approach. Therefore, to maximise profit, the best type must be selected based on cost and effectiveness. The present study compared three common products of hCG on blood sexual hormone, reproductive performance, and fry production per kg female. Four groups were designed to be: Group1: Untreated group to (control), Group2, Group3, and Group4, the brood-stock was hormonally induced with Choriomon®, Chorionic Gonadotropin, and Epifasi®, respectively. Both males and females received the same single dose of hCG (1500 IU)/kg of biomass. 80 brood-stock (40 female + 40 male) were used and distributed in two replicates in 8 square concrete ponds (water volume: 2.4 m3) each tank was randomly stocked at a rate of (5 males + 5 females). A single dose of hCG was injected intramuscularly at an angle of 45 degrees above the lateral line towards the tail. 24 hr after the injection blood sampling was drawn and samples of testes and ovaries were collected to measure reproductive indices and analyse chemical composition. Results showed superiority in all indicators of reproductive physiology that related to reproductive between hCG-treated brood-stock and untreated group. Besides, brood-stock injected with Choriomon® was the best in fry production (34587 larvae/kg brood stock) followed by Chorionic Gonadotropin and Epifasi®, respectively, while the Chorionic Gonadotropin group had the highest dose cost for producing 1000 fry.